2020
DOI: 10.1002/jssc.202000013
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet transforms in separation science for denoising and peak overlap detection

Abstract: Wavelet transform is a versatile time‐frequency analysis technique, which allows localization of useful signals in time or space and separates them from noise. The detector output from any analytical instrument is mathematically equivalent to a digital image. Signals obtained in chemical separations that vary in time (e.g., high‐performance liquid chromatography) or space (e.g., planar chromatography) are amenable to wavelet analysis. This article gives an overview of wavelet analysis, and graphically explains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Figure 4a-d explains exactly the different comparisons made and the results obtained for 10 subjects. In addition, Figure 4 shows a comparison between Daubechies (db) and Symlet (sym) with the order N (2,4,6,8) in relation to threshold techniques. First, we found that db2 is better than db (4,6,8) in Sureshrink, db4 is better than db (2,6,8) in Neighblock, db4 is better than db (2,6,8) in Rigrsure, and db8 is better than db (2,4,6) in Sqtwolog.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 4a-d explains exactly the different comparisons made and the results obtained for 10 subjects. In addition, Figure 4 shows a comparison between Daubechies (db) and Symlet (sym) with the order N (2,4,6,8) in relation to threshold techniques. First, we found that db2 is better than db (4,6,8) in Sureshrink, db4 is better than db (2,6,8) in Neighblock, db4 is better than db (2,6,8) in Rigrsure, and db8 is better than db (2,4,6) in Sqtwolog.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Figure 4 shows a comparison between Daubechies (db) and Symlet (sym) with the order N (2,4,6,8) in relation to threshold techniques. First, we found that db2 is better than db (4,6,8) in Sureshrink, db4 is better than db (2,6,8) in Neighblock, db4 is better than db (2,6,8) in Rigrsure, and db8 is better than db (2,4,6) in Sqtwolog. Second, sym2 is better than sym (4,6,8) in Sureshrink, sym4 is better than sym (2,6,8) in Neighblock, sym8 is better than sym (2,4,6) in Rigrsure, and sym8 is better than sym (2,4,6) in Sqtwolog.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the detection of these components in the signal has become an important content in fault diagnosis. For example, in the fault diagnosis of rolling bearings and gears, the appearance of periodic pulse components often indicates the occurrence of faults.Wavelet transform is the convolution operation between the original signal and the wavelet function, which actually measures the similarity degree between the signal and the wavelet function [12]. In this way, by selecting different wavelet basis functions, the content of the components that are close to the wavelet shape in the signal could be detected, which can be used to detect the characteristic components in the signal.…”
Section: 1continuous Wavelet Transformmentioning
confidence: 99%